"No disease for the others": How COVID-19 data can enact new and old alterities. Issue 2 (July 2020) - Pelizza, Annalisa
The COVID-19 pandemic invites a question about how long-standing narratives of alterity and current narratives of disease are entwined and re-enacted in the diagnosis of COVID-19. In this commentary, we discuss two related phenomena that, we argue, should be taken into account in answering this question. First, we address the diffusion of pseudoscientific accounts of minorities' immunity to COVID-19. While apparently praising minorities' biological resistance, such accounts rhetorically introduce a distinction between "Us" and "Them, " and in so doing produce new and re-enact old narratives of alterity. Second, these unsubstantiated narratives thrive on fake news and scarcity of data. The second part of this commentary thus surveys the methods through which the COVID-19 test is administered in various countries. We argue that techniques used for data collection have a major role in producing COVID-19 data that render contagion rates among migrants and other minorities invisible. In the conclusion, we provide two recommendations about how COVID-19 data can instead potentially work towards inclusion.